2019
DOI: 10.1111/1751-7915.13457
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Hg phytoavailability in soil using Hg‐volatilizing bacteria and biochar and the response of the native bacterial community

Abstract: Summary Biological approaches are considered promising and eco‐friendly strategies to remediate Hg contamination in soil. This study investigated the potential of two ‘green’ additives, Hg‐volatilizing bacteria (Pseudomonas sp. DC‐B1 and Bacillus sp. DC‐B2) and sawdust biochar, and their combination to reduce Hg(II) phytoavailability in soil and the effect of the additives on the soil bacterial community. The results showed that the Hg(II) contents in soils and lettuce shoots and roots were all reduced with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
(99 reference statements)
0
8
0
Order By: Relevance
“…Moreover, heavy metal(loid)s are harmful to microorganisms due to their long biological half-life, toxicity, and non-biodegradability (Abdu et al 2016). The microbial abundance and community diversity of metal(loid) contaminated soils are significantly lower than those of clean soils due to heavy metal(loid) stress (Chang et al 2019;Wan et al 2022). The addition of biochar amendments to soil facilitates the stabilization of heavy metal(loid)s, reducing their bioavailability and mitigating stress to microorganisms, ultimately contributing to the growth and metabolism of microorganisms, and improving both their abundance and activity.…”
Section: Heavy Metal(loid)s Immobilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, heavy metal(loid)s are harmful to microorganisms due to their long biological half-life, toxicity, and non-biodegradability (Abdu et al 2016). The microbial abundance and community diversity of metal(loid) contaminated soils are significantly lower than those of clean soils due to heavy metal(loid) stress (Chang et al 2019;Wan et al 2022). The addition of biochar amendments to soil facilitates the stabilization of heavy metal(loid)s, reducing their bioavailability and mitigating stress to microorganisms, ultimately contributing to the growth and metabolism of microorganisms, and improving both their abundance and activity.…”
Section: Heavy Metal(loid)s Immobilizationmentioning
confidence: 99%
“…In general, the relative abundance changes in dominant groups Acidobacteria, Actinobacteria, Bacteroidetes, Firmicutes, Gemmatimonadetes, and Proteobacteria at the phylum level are found in Pb, As, Cd, and Hg contaminated soils after the biochar amendments addition. Besides these dominant groups, the relative abundance changes in Chloroflexi and Patescibacteria are easily detected in Pb contaminated soils (Liu et al 2022a;Wan et al 2022), the relative abundance changes in Chloroflexi and Planctomycetes are easily monitored in As contaminated soils (Irshad et al 2022;Liu et al 2017b;Zhang et al 2020a), the relative abundance changes in Chloroflexi, Planctomycetes, and Patescibacteria are easily observed in Cd contaminated soils (Liu et al 2020b(Liu et al , 2022aZhou et al 2022), and the relative abundance changes in Planctomycetes are easily measured in Hg contaminated soils after the biochar amendments addition (Chang et al 2019). At the genus level, the relative abundance changes in Bacillus, Flavisolibacter, Sphingomonas, Clostridium, Nitrospira, and Nocardioides are generally observed in Pb-contaminated soils after biochar addition (Liu et al 2022a;Wei et al 2022;Zhang et al 2020a), while the relative abundance changes in Bacillus, Flavisolibacter, Clostridium, Nitrospira, Nocardioides, and Gemmatimonas are generally observed in As contaminated soils (Irshad et al 2022;Liu et al 2017b;Zhang et al 2020a), and the relative abundance changes in Bacillus, Flavisolibacter, Sphingomonas, Clostridium, Nitrospira, Nocardioides, Massilia, and Lysobacter are generally detected in Cd contaminated soils (Liu et al 2022a;Qi et al 2022;Wu et al 2019a;Zhou et al 2022), while the relative abundance changes in Sphingomonas, Clostridium, Nitrospira, Nocardioides, Massilia, and Gemmatimonas are generally detected in Hg contaminated soils (Chang et al 2019).…”
Section: Heavy Metal(loid)s Immobilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, Gram-positive bacteria are recognised as most effective in the removal of HMs due to presence of glycoproteins compared to Gram-negative bacteria comprising phospholipids and lipopolysaccharides (Das et al, 2008;Gourdon et al, 1990). Chang et al, (2019) had shown that augmenting biochar with Pseudomonas sp. DC-B1 and Bacillus sp.…”
Section: Bactoremediation Mycoremediation and Phycoremediationmentioning
confidence: 99%
“…The relative abundance of Bacteroides and Firmicutes was increased as compared to the Proteobacteria members in biochar applied soils. In a different study, biochar application increased the abundance of a particular genus of bacteria such as Haliangium [ 195 ] and Asticcacaulis [ 196 ].…”
Section: Application Of Engineered Biochar In Different Fieldsmentioning
confidence: 99%